Heart Matters: a study protocol for a community based randomized trial aimed at reducing cardiovascular risk in a rural, African American community - Giselle Corbie-Smith; Crystal Wiley-Cene; Kiana Bess; Tiffany Young; Gaurav Dave; Katrina Ellis; Stephanie M. Hoover; Feng-Chang Lin; Mysha Wynn; Shirley McFarlin; Jamie Ede (BMC, 2018)
Abstract Background African Americans living in the rural south have the highest prevalence of cardiovascular disease (CVD) risk in the United States. Given this geographic and racial disparity, intervention implementation needs to be evaluated for effectiveness and feasibility with African Americans in the rural south. Methods The trial developed out of a community-based participatory research partnership, Project GRACE, and community partners who are collaborators throughout the study. Heart Matters is a randomized stepped wedge trial that will assess the effectiveness of a 12-month behavioral change intervention adapted from PREMIER, an evidence-based treatment targeting multiple CVD risk factors. 140 participants will be recruited through 8 community- or faith-based organizations to participate in the intervention. Through matched pair randomization, organizations will be randomized to begin immediately after baseline data collection (Arm 1) or delayed 6 months (Arm 2). Data collection will occur at baseline, 6, 12, and 18 months. The primary outcome is change in body weight. In addition to assessing effectiveness, the study will also evaluate process and feasibility outcomes through quantitative and qualitative data collection. Discussion This study will contribute to CVD prevention research and likely have a positive impact on the rural, African American community where the trial occurs. Our study is unique in its use of community partnerships to develop, implement, and evaluate the intervention. We expect that this approach will enhance the feasibility of the trial, as well as future dissemination and sustainability of the intervention. Trial registration Clinical Trials, NCT02707432. Registered 13 March 2016.